Evaluation of performance characteristics of a novel hydrogen-fuelled free-piston engine generator. (24th September 2021) - Ngwaka, Ugochukwu; Smallbone, Andrew; Jia, Boru; Lawrence, Christopher; Towell, Ben; Roy, Sumit; KV, Shivaprasad; Roskilly, Anthony Paul
Abstract: In this work, we present the experimental results obtained from hydrogen fuelled spark-ignited dual piston free-piston engine generator (FPEG) prototype operated in two-stroke and four-stroke mode. The FPEG testing was successfully conducted at 3.7 compression ratio, engine speed between 5 Hz and 11 Hz and with different equivalence ratios. The FPEG technical details, experimental set-up and operational control are explained in detail. Performance indicators show that both equivalence ratio and engine speed affect the engine operation characteristics. For every set of specified FPEG parameters, appropriate range of equivalence ratio is recommended to prevent unwanted disturbance to electric generator operation. Both two-stroke and four-stroke cycle mode were tested, and the results showed different combustion characteristics with the two thermodynamic cycles. Four-stroke cycle mode could operate with indicated thermal efficiency gain up to 13.2% compared with the two-stroke cycle. Graphical abstract: Image 1 Highlights: Experimental results from hydrogen powered free piston engine generator. Comparison of results from two-stroke and four-stroke mode of operations. For similar operating conditions four-stroke performed better than two-stroke mode. Maximum power output was 650 W with negligible NOx emission.